2017
DOI: 10.3390/en10111723
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Optimum Heat Transfer Coefficient and Temperature Rise Analysis for a Lithium-Ion Battery under the Conditions of Harbin City Bus Driving Cycles

Abstract: This study investigated the heat problems that occur during the operation of power batteries, especially thermal runaway, which usually take place in high temperature environments. The study was conducted on a ternary polymer lithium-ion battery. In addition, a lumped parameter thermal model was established to analyze the thermal behavior of the electric bus battery system under the operation conditions of the driving cycles of the Harbin city electric buses. Moreover, the quantitative relationship between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…Moreover, a lumped parameter thermal model was constructed to investigate the thermal behaviour of the battery system. The outcomes demonstrated that the heat transfer coefficient is the third power subordinate of the ambient temperature [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a lumped parameter thermal model was constructed to investigate the thermal behaviour of the battery system. The outcomes demonstrated that the heat transfer coefficient is the third power subordinate of the ambient temperature [10].…”
Section: Introductionmentioning
confidence: 99%
“…Temperature increase analysis and optimal heat transfer coefficient were determined for a polymer lithium-ion battery under bus-driving cycle's condition [10]. This investigation studied the heat problems, which arise during the working of power batteries, especially high temperature environments.…”
Section: Introductionmentioning
confidence: 99%
“…An important aspect in the operation of electric vehicles is the possibility of using it in various climatic conditions. Studies on this issue were mainly related to the use of appropriate devices such as heat pumps [44,45], air conditioning systems, [46][47][48] and other systems [49] used to condition elements of the electric drive system, driver's cab, and passenger compartment. The last group of publications offers analyses of the results obtained during the operation of urban electric buses under real conditions [50][51][52][53][54].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the speed of the battery's side reaction will accelerate when the temperature is too high, and the capacity of the battery will be greatly reduced. A battery fire, explosion, or other safety incidents can also happen due to a high temperature [5][6][7].…”
Section: Introductionmentioning
confidence: 99%